2020
DOI: 10.1371/journal.pone.0236519
|View full text |Cite
|
Sign up to set email alerts
|

A computational model of stem cell molecular mechanism to maintain tissue homeostasis

Abstract: Stem cells, with their capacity to self-renew and to differentiate to more specialized cell types, play a key role to maintain homeostasis in adult tissues. To investigate how, in the dynamic stochastic environment of a tissue, non-genetic diversity and the precise balance between proliferation and differentiation are achieved, it is necessary to understand the molecular mechanisms of the stem cells in decision making process. By focusing on the impact of stochasticity, we proposed a computational model descri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 102 publications
(163 reference statements)
0
23
0
Order By: Relevance
“…Considering these facts, and inspired by previous studies that revealed the impact of regulatory networks on the stability of biological systems 6 , 10 , 23 , 29 , 35 39 , in our model, we introduce multi-stable regulatory networks as the internal decision-makers of dividing cells. Here, a set of ordinary differential equations (ODEs) are defined as the typical mathematical tool to study, and describe the regulatory circuitries 7 , 32 , 40 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Considering these facts, and inspired by previous studies that revealed the impact of regulatory networks on the stability of biological systems 6 , 10 , 23 , 29 , 35 39 , in our model, we introduce multi-stable regulatory networks as the internal decision-makers of dividing cells. Here, a set of ordinary differential equations (ODEs) are defined as the typical mathematical tool to study, and describe the regulatory circuitries 7 , 32 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering all the facts discussed before and focusing on the impact of stochasticity, here, we propose a computational model to reveal the mechanism which maintains the proliferation/differentiation balance as well as the spatial pattern in a hypothetical normal adult tissue. The proposed model is defined based on six material principles discussed in 7 , 13 and reconsidered as follows: (1) stochasticity is an inevitable part of any living cell 5 , 7 , 13 , 38 , 45 49 . (2) Two major sources of stochasticity, the non-deterministic position of the cell division plane and nonuniform distribution of determinants in the cell lead to the random distribution of the cytoplasmic molecules among daughter cells during cell division 7 , 13 , 50 56 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations